Membrane technology application in the framework of zero emission concept - Vuk Rajović; Jelena Marković; Aleksandar Jokić; Jelena Ilić (Zaštita Materijala)
The Zero emissions concept envisages all industrial inputs being used in final products or converted into value-added inputs for other industries or processes. In this way, industries are reorganized into clusters such that each industry's wastes / by-products are fully matched with the input requirements of another industry, and the integrated whole produces no waste of any kind. This technique is based on the well-established economic analysis tool known as the input/output approach. In the framework of the zero emission concept capture of CO2 plays an important role. CO2 can be captured and permanently stored, or it can be re-used. Carbon sequestration is a two-step process where the capture of CO2 from a gas stream is followed by its permanent storage. The capture step contributes 75% to the overall carbon sequestration process cost. For this reason, the scientific community has paid a great attention to the development of new processes for CO2 capture. Currently, there is a wide range of technologies to separate CO2 from gas streams. They are based on different physical and chemical processes including absorption, adsorption, cryogenics and membrane technology. The choice of a suitable technology depends on the characteristics of the flue gas stream and, as a consequence, on the power plant technology. As an alternative to conventional process es for CO2 separation and capture, membrane technology shows great potentiality for CO2 capture owing to its easy applicability, efficiency, flexibility, ability to maintain high CO2 pressure and to perform separations at low energy penalties. CO2-selective membranes allow separation of CO2 from different gas streams, such as: flue gas (post-combustion system), natural gas (natural gas processing) and hydrogen (pre-combustion systems) or oxygen from nitrogen (in an oxyfuel combustion system). In the framework of zero emission concept, this paper gives an overview and analysis of the types of membranes used and membrane technology application in CO2 capture from the point of cost and energy consumption.